PTU-177 Retrospective Audit of Management of Patients Admitted to Intensive Care unit (ITU) with Severe Acute Pancreatitis(SAP). (4th June 2013) - Jalil, O; Iqbal, A; Patel, C; Radwan, R; Rasheed, A
Abstract : Introduction: To compare management strategies and mortality of patients admitted to ITU with SAP against national standards and study the group who succumbed to their disease in detail to identify the most accurate prognostic indicators in this group of patients. Methods: Retrospective audit of management and outcome of consecutive patients admitted to ITU with SAP during 2007–2010. The development of necrosis and organ failure(OF)was recorded. Patients were classified into four groups: I (No necrosis or OF), II (sterile necrosis or transient OF), III (infected necrosis or persistent OF) and IV (infected necrosis and persistent OF). Results: Fifty one patients were admitted to ITU with SAP (APACHE II > 8, modified Glasgow score > 3). All cases fulfilled the Atlanta criteria of SAP. Median age: 66 ± 17.5. The overall mortality rate was 38% (n-19) above national standard of 30%. All 7 patients in group IV died, 5 of them underwent necrosectomy and 1 had CT guided drainage of infected acute fluid collection. The table shows the total number of patients and respective mortality in each group. Neither antibiotics nor nutritional support had significant impact on survival. Outcome (death) correlated with organ dysfunction criteria (Atlanta criteria and APACHE II score). Conclusion: While the presence of infected necrosis or persistent organ failure in SAP (group III) is associated with high mortality, the combination of "infected necrosis and persistent organ failure" (group IV) is uniformly fatal. Further research is necessary to confirm our findings and to explore ways of optimising patients in group III to improve survival. Disclosure of Interest: None Declared.